Widening the Caribbean Community : issues and considerations (UN. ECLAC Port of SpainTT, 1992)
Provides a brief description of the Caribbean Community and examines its trade and functional cooperation activities. Looks at the countries suggested for inclusion in the proposed Association of Caribbean States and describes their present relationship with CARICOM. Revisits the question of deepening as opposed to widening the integration movement and makes suggestions as to the way forward for the inclusion of non-CARICOM countries.
DC